Fibrinolysis and beyond: bridging the gap between local and systemic clot removal - Knauer, K; Huber, Roman (Frontiers in Neurology, 2011)
Recanalization methods in ischemic stroke have been progressively expanded over the past years. In addition the continuous development of specialized mechanical devices for thrombectomy a broad spectrum of new drugs has been tested: Both options, novel drugs as well as new devices, can be employed independently of each other, but in most cases a combination of the two with the standard treatment of intravenous fibrinolysis is applied. Until recently, a large number of case series have been performed to investigate the effects of various drugs and interventions, but only a few trials have been conducted to determine the optimal conditions for combining both procedures. This review surveys the different systemic and endovascular vessel reopening practices and their major bridging techniques.